Public Speaking Learning in Elementary School: Strategies to Overcome Effective Communication Rigidity - Ade Novita S.; Siti Hana M. Saboy; Istiqamah; Nurhalisa (Pengembangan Pendidikan dan Pembelajaran Sekolah Dasar, 2025)
The research aims to determine strategies to overcome effective communication rigidity through habituation to learning public speaking. This research is qualitative-quantitative descriptive type with data collection techniques including direct observation and interviews involving teachers and students of grades V and VI SDN 6 Tolitoli and distributing questionnaires. The research findings confirm that a lack of motivation and insufficient speaking habits in classroom forums are the dominant factors contributing to students’ speaking rigidity in both classes, with percentages ranging from approximately 70% to 77%, although all other factors also exert strong influences, each exceeding 70%. In responding to these findings, five effective strategies were determined that teachers can apply gradually in increasing students' effective communication habits as well as effective in overcoming public speaking rigidity, which begins with providing speaking habits in discussion forums/direct speaking practices, building confidence, and advanced assignments (practices in intracurricular, extracurricular, and community forums). Based on the scope of this strategy, it is named as an effective communication habituation strategy. Through the implementation of these strategies, it can contribute effectively in improving students' public speaking skills to be more confident and able to channel their ideas in a wider public forum.